Penerapan Model Pembelajaran Novick Berbantuan E-Booklet Berbasis Anyflip Terhadap Pemahaman Konsep Fisika Siswa Kelas XI SMA Negeri 3 Rambah Hilir - Asra, Azmi; Hasriah, Sri Leni; Daruwati, Ika (JURNAL PENDIDIKAN ROKANIA, 2024)
This study aims to determine the application of the Novick learning model using anyflip-based e-booklet media to students’ understanding of physics concepts. This research was conducted at SMA Negeri 3 Rambah Hilir in the even semester of the 2022/2023 Academic Year. This type of research is a quantitative research with an experimental research approach, with a one-grup pretest-posttest design. The sample in the research was students of class XI IPA 1 Academic Year 2022/2023, a total of 35 students using of purposive sampling technique. The instruments used were validation sheets and multiple choice question tests. Data analysis was carried out using the learning completeness test. Classical un and gain test. Based on the calculation of the pretest classical learning completeness is 0% while for the posttest completeness is 91.42% and the average gain value is 0.75 with high criteria. This shows that by applying the Novick learning model assisted by Anyflip-based e-booklet can improve learning outcomes students in the form of understanding the concept in class XI IPA 1 SMA Negeri 3 Rambah Hilir on the material of optical instruments.